2017
DOI: 10.1007/s00431-017-2913-0
|View full text |Cite
|
Sign up to set email alerts
|

A three-step diagnosis of pediatric pneumonia at the emergency department using clinical predictors, C-reactive protein, and pneumococcal PCR

Abstract: A model incorporating clinical signs and laboratory markers can effectively assess the risk of having pneumonia. Children with negative clinical signs and low CRP are at a low risk of having pneumonia. For children with positive clinical signs and high CRP, a positive blood pneumococcal PCR can more accurately confirm the diagnosis of pneumonia. What is Known: • Distinguishing between bacterial and viral pneumonia in children is challenging. • Reducing the inappropriate use of antibiotics is a priority. What i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 47 publications
2
33
0
Order By: Relevance
“…was even true for PCT and CRP of Mp-positive CAP in comparison to viral CAP (RSV) as a subgroup of Mp-negative CAP. Similar trends have been observed in previous CAP studies for CRP, WBC count, and ANC [23,[39][40][41][42][43], and recently for PCT with median levels from 0.05 to 0.19 μg/L in CAP considered to be caused by Mp [39][40][41]44]. A study with conflicting results suggesting higher PCT levels associated with Mp may be hampered by diagnostics [45].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…was even true for PCT and CRP of Mp-positive CAP in comparison to viral CAP (RSV) as a subgroup of Mp-negative CAP. Similar trends have been observed in previous CAP studies for CRP, WBC count, and ANC [23,[39][40][41][42][43], and recently for PCT with median levels from 0.05 to 0.19 μg/L in CAP considered to be caused by Mp [39][40][41]44]. A study with conflicting results suggesting higher PCT levels associated with Mp may be hampered by diagnostics [45].…”
Section: Discussionsupporting
confidence: 86%
“…A study with conflicting results suggesting higher PCT levels associated with Mp may be hampered by diagnostics [45]. A PCT cutoff of <0.25 μg/L reached the best discriminatory power in differentiating Mp-positive from Mp-negative children with CAP, which is supported by previous studies [39][40][41]44]. Only 1 Mp-positive patient had a PCT level of 0.55 μg/L and was above this cutoff.…”
Section: Discussionmentioning
confidence: 57%
“…Curiously, PCT and CRP were studied in combination in 2 studies included in the present meta-analysis [19, 32], but the reported results were not sufficient to demonstrate a combined effect; rather, the authors only tested whether 1 parameter is a better marker than the other. In 1 study included here, performed in Italy, the authors identified a significant positive correlation between serum PCT levels and the main markers of inflammation such as CRP, percentage of neutrophils, and WBC [24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, researchers have proposed combining clinical signs and laboratory markers to assess an individual’s risk of contracting pneumonia. For example, high levels of CRP and procalcitonin accompanied by unilateral hyperventilation and grunting were associated with pneumonia ( 302 ). On the other hand, children with no clinical signs of pneumonia and low CRP results were at a lower risk for pneumonia.…”
Section: Diagnosis Age-dependent Response Prevention and Disease Pmentioning
confidence: 99%
“…The use of PCR for diagnosis is also being developed. A positive blood pneumococcal PCR can more accurately confirm the diagnosis of pneumonia ( 302 ). PCR has been used to detect pneumolysin in whole blood samples ( 303 ).…”
Section: Diagnosis Age-dependent Response Prevention and Disease Pmentioning
confidence: 99%